Ego-resilience and health-related quality of life after acquired Upper Limb Amputation - Lauren A. Trent; Anna Zanotto (PLoS ONE, 2026)
Purpose The purpose of this study was to examine the relationships between demographic variables, ego-resilience and health-related quality of life (HRQoL) for individuals with upper limb amputations. As HRQoL continues to be an important measure of rehabilitative success, determining universal factors which correlate to and may predict HRQoL becomes more important in the clinical space. Methods A sample of 90 previously administered outcomes from patients at a national upper limb prosthetic provider in the United States were gathered. The outcome measure, the Wellness Inventory, captured patient-reported data to screen for mental health status including ego-resilience, PTSD, depression, coping mechanisms. Scores from the Orthotics and Prosthetics Users’ Survey (OPUS) HRQoL as well as the Ego-Resilience Scale (ER89) were utilized in this study, as well as pertinent demographic data. Comparative analyses were conducted on the data gathered. Results HRQoL and Ego-Resilience scores were analyzed alongside demographic factors: gender (77.8% male), age at time of amputation (mean age 38, SD = 12.9), level of amputation, ethnicity and marital status. Correlational analysis showed positive relationship between ego-resilience and HRQoL (ρ = 0.332, p = .002). Simple linear regression analysis found a significant relationship between ethnicity and HRQoL (β = 4.237, p = .047), and ego-resilience and HRQoL (β = 0.910, p=<.001). The multiple linear regression model identified ego-resilience and ethnicity as predictors for HRQoL (adjusted R² = .129, F = 7.576, p=<.001). Conclusion Based on the findings in this study, ego-resilience has been identified as a significant predicting factor for HRQoL. Higher ego-resilience score and trait likely will result in higher HRQoL scores. Understanding of how demographic variables, such as ethnicity, may directly or indirectly impact HRQoL can also be beneficial in the recovery process.